IMMERSIVE APPIAN WAY HEALTH INFRASTRUCTURE: HUMAN CENTRIC DIGITAL TWIN (THE PAAA ARCHEOLOGICAL PARK OF THE APPIAN WAY 12KM STATE-OWN SECTION, UNESCO CANDIDATURE) - R. Brumana; S. Quilici; L. Oliva; M. Previtali; D. Attico; D. Attico; F. Roncoroni; C. Stanga (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
From Rome to Benevento, the Appian Way (Via Appia Antica) was born as a military road, 'Regina Viarum'. In 312 b.C., consul Appio Claudio extended the infrastructure for 132 miles to Capua. Many transformations and integration occurred across the centuries, resulting in a unique multi-stratified world heritage (landscape, architecture, archaeological remains and tombs along the military way). In the 19th century, Luigi Canina conceived the Appian Way as an outdoor museum, realizing a first state-own section along the 12km here surveyed and described. This year, the Ministry of Culture (MIC) has launched the UNESCO nomination for the road. The article discusses aspects of the mass digitization undertaken by the Parco Archeologico dell'Appia Antica (PAAA, the Archaeological Park of the Appian Way). The aim is to build a Digital Twin of the infrastructure supporting knowledge enhancement, preservation, design, communication and fruition. A virtual space where digital technologies and eXtended Reality are the digital arms of the contemporary Vitruvian humanistic mission and vision of the PAAA Appian Way as a source of wealth and healthiness for all the users and visitors.